A study of Ki-67 expression and its clinicopathological determinants in nondysplastic oral leukoplakia - Krishnendu Mondal; Rupali Mandal; Badal Chandra Sarkar (Wolters Kluwer Medknow Publications, 2016)
Context: Oral cancer is the third most prevalent malignancy in India. Leukoplakia is its most common precursor lesion. Aims: This study aimed at evaluation of the Ki-67 expression and thereby detection of the dysplastic potential in histopathologically nondysplastic oral leukoplakia (OL). Secondarily, another purpose was to correlate various clinicopathological factors with the labeling indices (LIs) of Ki-67 in those cases as well. Settings and Design: In total, 97 OL cases were examined. Relevant clinical and demographic information was retrieved from the pro forma, prefilled by the patients themselves during their first visit. Subjects and Methods: Ki-67 immunohistochemical staining was performed on paraffin-embedded tissue samples. Its LIs were calculated and correlated with different clinicopathological parameters using statistical software SPSS version 16.0. Results: 58.8% (57 cases) lesions exhibited a Ki-67 positivity of ≤5%, and 25.8% (25 cases) lesions exhibited it in the range of 6%-25%. Only 15 (15.4%) patches were stained positively between 26% and 60%. Patients' age beyond 50 years, nonhomogeneous leukoplakia, and tobacco addiction were the significant risk factors for high Ki-67 scores (P < 0.05). Conclusions: Ki-67 is an essential immunohistochemical marker for epithelial dysplasia in OL, especially when the conventional histopathology fails to appreciate the same. In this purpose, Ki-67 labeling on a routine basis delivers the most convenient results for patients aged above 50 years, and/or addicted to tobacco products, and/or suffering from nonhomogeneous patches.